Microsoft Word Training for Students of the Manggarai State 11Pusat Kegiatan Belajar Masyarakat South Jakarta - Nawindah Nawindah; , Ratna Ujiandari; Putri Hayati (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Current technological developments require expertise in managing good words for making job applications, school assignments, making learning materials and other needs that are beneficial to society. Pusat Kegiatan Belajar Masyarakat (PKBM) Negeri 11 Manggarai is one of the institutions that has services for information through education, one of which is Pursue Package C. The unavailability of computer laboratories is a limitation in improving skills in using computer applications, cooperation between PKBM Negeri 11 Manggarai and Universitas Budi Luhur The Faculty of Information Technology has jointly provided an increase in the ability to use the Microsoft Word application for PKBM Negeri 11 Manggarai Jakarta students. The training methods used are preparation, implementation and evaluation. The result of the training activity was an increase in the level of understanding of the 16 participants who were present, as many as 13 participants who already understood and could use the Microsoft Word application.